Profile and Correlation Analysis of Environmental Literacy Domains at Adiwiyata School - Nur Ita Rahmawati; Ali Mustofa; Imas Cintamulya (Bioedukasi: Jurnal Pendidikan Biologi, 2025)
Adiwiyata, an environmental education program is one of the educational initiatives in Indonesia to address environmental challenges. The Adiwiyata program is a method of integrating environmental literacy into environmental learning. This research aims to determine the environmental literacy profile of Adiwiyata School students and the correlation between various environmental literacy domains. The research used a Quantitative Descriptive method with a population of class IX junior high school students. A sample of 100 students was determined using Purposive Sampling Technique. The research results show that the Adiwiyata curriculum has an impact on students' environmental literacy. With an environmental literacy score of 76.4, this student is included in the high category. The environmental literacy domain shows results in the medium and high categories; the domain of students' pro-environmental attitudes and behavior shows quite good results and supports the environment; and the knowledge domain shows moderate results. Based on the correlation test between domains, it was concluded that there was a relationship between knowledge, attitudes, pro-environmental behavior, and increasing students' environmental literacy. This shows that an increase in one of these factors tends to be associated with an increase in environmental literacy.